Health behavior practiced during the quarantine of the Coronavirus / COVID-19 among students of the College of Sports Sciences at Mutah University - Thuneibat, Baker Suleiman (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to determine the level of health behavior practiced by students of the Faculty of Sports Sciences at Mutah University during the quarantine period for the Coronavirus/COVID-19. The study sample consisted of 120 randomly selected male and female students from the Faculty of Sports Sciences at Mutah University. Methods: The study used the descriptive approach, utilizing survey methods and following scientific steps and procedures suitable for this research. Results: The findings of this study indicated that the students of the Faculty of Sports Sciences at Mutah University exhibited a high level of healthy behavior during the quarantine for the Coronavirus/COVID-19, with a mean score of 3.86 and a standard deviation of 1.269. Furthermore, the study results revealed no statistically significant differences (α≤0.05) in the practiced health behavior during quarantine for the Coronavirus/COVID-19 among students of the Faculty of Sports Sciences at Mutah University based on variables such as gender, academic department, academic level, or academic appreciation. Conclusion: It is crucial to maintain a high level of healthy behavior by adhering to the instructions and guidelines recommended by the World Health Organization or the relevant ministries dealing with the COVID-19 pandemic.